Assessment of lipid abnormalities and Cardiovascular Risk indices in Type 2 Diabetes Mellitus - Baral, Sushil; Hamal, Achyut Bikram; BK, Shyam Kumar; Gupta, Sandeep; Sigdel, Manoj; Mandal, Laxman Prasad (Asian Journal of Medical Sciences, 2019)
Background: Incidence of cardiovascular events is increased to two to four times among diabetic patients when compared with non-diabetic. Dyslipidaemia in diabetes is major risk factor for cardiovascular events. Atherogenic indices have been used as major laboratory measures in clinical practice to assess cardiovascular risk. Recent studies, have shown that non-high-density lipoprotein cholesterol and other atherogenic indices is like or better than LDL-C alone in the prediction of CVD incidence and mortality. Aim and Objectives: The aim of this study is to assess the lipid abnormalities with cardiovascular risk using atherogenic coefficient (Ac), Cardiac Risk Ratio (TC/HDLc and LDLc/HDLc), TG/HDLc and Non- HDL in diabetes patients. Materials and Methods: A cross-sectional descriptive study conducted at Bir hospital (tertiary care center) Nepal. Patients diagnosed as diabetes with age 30 years or above were selected in this study during a period of 1 yr. Results: The mean age of the patients enrolled was 55.08±1.11 (34-81) year with male (52 %) to female (48%) ratio is 1.08:1. In this study the mean Non HDLc was 165.24±43.40 mg/dl (65-323) and AC was 4.0±1.09. The finding of AC was slightly higher in female compare to male i.e mean ±S.D 4.07±1.31 and 3.94±1.15. This study show the strong correlation of Non HDLc with total cholesterol (r=.990, p=0.000), LDLc(r=.602,p=0.000),TG (r=.411,p=0.000), LDLc/HDLc (r=.580,p=0.000),TC/HDLc ((r=.866,p=0.000), TG/HDLc (r=.390,p=0.000) and AC (p=0.866). Conclusion: The association between abnormal lipid levels and cardiovascular risk is evident among patients with diabetes mellitus. In this study there is the correlation with FBS, Non HDL-c cholesterol, Cardio risk ratio, TG/HDLc, Atherogenic coefficient. Hence Non-HDL cholesterol and Atherogenic indices proves to be more sensitive and a better predictor of cardiovascular events in diabetes patients.